Serious reflections during the life and surprising adventures of Robinson Crusoe with his vision of the angelick world the Stoke Newington Edition - Defoe, Daniel 1660-1731 (Bucknell University Press, 2022)
Serious Reflections During the Life and Surprising Adventures of Robinson Crusoe with his Vision of the Angelick World, first published in 1720 and considered a sequel to The Farther Adventures of Robinson Crusoe, is a collection of essays written in the voice of the Crusoe character. Expressing Defoe's thoughts about many moral questions of the day, the narrator takes up isolation, poverty, religious liberty, and epistemology. Defoe also used this volume to revive his interest in poetry, not the satiric poetry of the early eighteenth century, but the more inspirational verse that appeared in some of his later works. Serious Reflections also includes an imaginative flight in which Crusoe wanders among the planets, a return to the moon voyage impulse of Defoe's 1705 work The Consolidator. Illuminating the ideas and philosophy of this most influential of English novelists, it is invaluable for any student of the period.
Description based on online resource; title from PDF title page (publisher's Web site, viewed 24. Mai 2022)
Keywords: LITERARY COLLECTIONS / General; Crusoe, Robinson (Fictitious character) -- Fiction